Search Patterns and Absorptive Capacity: A Comparison of Low- and High-Technology Firms from Thirteen European Countries - Christoph Grimpe; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Searching for externally available knowledge has been characterised as a vital part of the innovation process. Previous research has, however, almost exclusively focused on hightechnology environments, largely ignoring the substantial low- and medium-technology sectors of modern economies. We argue that low- and high-technology firms differ in their search patterns and that these moderate the relationship between innovation inputs and outputs. Based on a sample of 4,500 firms from 13 European countries we find that search patterns in low-technology industries focus on market knowledge while they are built around differences in technology sourcing activities for high-technology industries.
Keywords: O32; L60; 330; Absorptive capacity; search strategies; low-; medium- and high-technology sectors; open innovation; Informationsverhalten; Wissen; Innovationsmanagement; Hochtechnologiesektor; Low-Tech; Vergleich; EU-Staaten